Instant-incidental-close-loop scheme to improve battery life in wireless sensor applications - Yopi Sopian; Faizal Arya Samman; Muhammad Niswar (Bulletin of Electrical Engineering and Informatics, 2026)
This work presents a simple new idea for implementing algorithms in microcontrollers that govern duty cycle transition settings in wireless sensors in closed-loop circuits that run on batteries. The switching time controlled to get end point and average duty-cycle (STEADY) method is used. Duty cycle regulation algorithms are used by instantaneous incidental closed loop (IICL) schemes to regulate current flow in circuits that serve as power consuming loads, facilitating quick and seamless transitions from open to closed loop. By using the STEADY algorithm on IICL, the issue of conserving battery energy to increase battery life can be resolved. Additional advantages of the STEADY algorithm include its low memory utilization of 4 Kbytes, or 12.5% of the 32 Kbytes of available memory slot, simplicity, and ease of implementation on microcontroller devices. Final testing using the IICL STEADY algorithm on the VD-2023 wireless DC voltage sensor prototype series shows that 627 mAh is more energy efficient than battery life in the IICL scheme without the STEADY algorithm applied, which is 26 minutes 37 seconds. The wake time is set to one millisecond, and the sleep time is set to one minute, and the battery power is provided by a 280 mAh battery. This results in a battery life of 8 hours 16 minutes 57 seconds.